Standardizing irrigation and planting schedule of salt tolerant rice (Oryza sativa) and wheat (Triticum aestivum) varieties for higher water productivity and yield in reclaimed sodic soils of Indo-Gangetic plains of India - KUMAR, PARVEEN; SINGH, AJAY; CHAUDHARI, S K; SHARMA, P C; SHARMA, D K (The Indian Journal of Agricultural Sciences, 2020)
Rice (Oryza sativa L.)-wheat (Triticum aestivum L.) system (RWS) grown on 10 m ha in the Indo-Gangetic Plains (IGP), is essential for food security of India. In IGP soil sodicity is very common and reclamation with gypsum is very expensive, so adoption of salt tolerant varieties of rice and wheat could be a better option. A field experiment was, therefore conducted for three years (2012-2015) in RWS to evaluate the performance of salt tolerant varieties under different dates of transplanting/sowing and irrigation scheduling. In kharif season, three irrigation scheduling, i.e. complete submergence/farmers practice (CS/FP), 3 days after disappearance of ponded water (DAD), and 5 DAD as horizontal factor and four transplanting dates (21 June, 1 July, 11 July, 21 July) as vertical factor conducted in strip plot design replicated thrice. In rabi season, three irrigation schedules, i.e. IW/CPE = 1.0, 0.8, and 0.6 as horizontal factor and four dates of sowing, i.e. 10 November, 20 November, 30 November, 10 December, as vertical factor and two salt tolerant wheat varieties, viz. KRL 210 and KRL 213 in subplots was conducted in strip split plot design, replicated thrice. Results indicated that salt tolerant rice variety Basmati CSR-30 can be transplanted on 1 July to get better yield attributes, highest grain yield (3.63 t/ha) and water saving (32.5%) by adopting irrigation scheduling of 5 DAD with highest irrigation water productivity (0.522 kg/m3). In rabi season, salt tolerant wheat varieties can be sown on 20 November following irrigation schedule of IW/CPE=1.0 (KRL-210: 6.76 t/ha and KRL-213: 6.88 t/ha) to get highest grain yield.